Education, Productivity and Gain. A View on the Critical Approaches to the Causal Chain the Human Capital Theory - Canals , Valérie; Jaoul-Grammare , Magali; Diebolt , Claude (Studia Oeconomica Posnaniensia, 2026)
This paper deals with the economic consequences of education for individuals who receive it. We focus on reference works of theories of human capital and on its critical approaches. Our aim is to question the various progresses of the relationship education-productivity-earning. In an extension we propose a first empirical evaluation applied to the French case